Long-range two-photon scattering spectroscopy ruler for screening prostate cancer cells. Issue 4 (16th February 2015) - Sinha, Sudarson Sekhar; Paul, Dilip K.; Kanchanapally, Rajashekhar; Pramanik, Avijit; Chavva, Suhash Reddy; Viraka Nellore, Bhanu Priya; Jones, Stacy J.; Ray, Paresh Chandra
Abstract : Development of a long-range TPS ruler for the screening of prostate cancer cells with sensitivity of 5 cells per mL level is demonstrated. Abstract : Optical rulers have served as a key tool for scientists from different disciplines to address a wide range of biological activity. Since the optical window of state of the art FRET rulers is limited to a 10 nm distance, developing long range optical rulers is very important to monitor real life biological processes. Driven by this need, the current manuscript reports for the first time the design of long-range two-photon scattering (TPS) spectroscopy rulers using gold nano-antenna separated by a bifunctional rigid double strand DNA molecule, which controls the spectroscopy ruler length. Reported data demonstrate that the TPS spectroscopy ruler's working window is a within a 25 nm distance, which is more than twice that of well recognized FRET optical ruler. A possible mechanism for the two-photon spectroscopy ruler's long range capability have been discussed using angle-resolved TPS measurement and FDTD simulations. Solution-phase experimental data demonstrated that a long-range TPS ruler using A9 aptamer can be used for the screening of prostate-specific membrane antigen (PSMA) (+) prostate cancer cells even at 5 cells per mL level. Reported result with PSMA (−) normal skin HaCaT cells indicate that TPS ruler based assay has the capability to enable distinction from non-targeted cell lines. Ultimately, the long range TPS ruler can be used towards better understanding of chemical and biological processes.